Respiratory and Cardiovascular Response during Electronic Control Device Exposure in Law Enforcement Trainees - VanMeenen, Kirsten M.; Lavietes, Marc H.; Cherniack, Neil S.; Bergen, Michael T.; Teichman, Ronald; Servatius, Richard J. (Frontiers in Physiology, 2013)
Objective: Law enforcement represents a large population of workers who may be exposed to electronic control devices (ECDs). Little is known about the potential effect of exposure to these devices on respiration or cardiovascular response during current discharge. Methods: Participants (N=23) were trainees exposed to 5 seconds of an ECD (Taser X26®) as a component of training. Trainees were asked to volitionally inhale during exposure. Respiratory recordings involved a continuous waveform recorded throughout the session including during the exposure period. Heart rate was calculated from a continuous pulse oximetry recording. Results: The exposure period resulted in the cessation of normal breathing patterns in all participants and in particular a decrease in inspiratory activity. No significant changes in heart rate during ECD exposure were found. Conclusions: This is the first study to examine breathing patterns during ECD exposure with the resolution to detect changes over this discrete period of time. In contrast to reports suggesting respiration is unaffected by ECDs, present evidence suggests that voluntary inspiration is severely compromised. There is no evidence of cardiac disruption during ECD exposure.